Renaissance now!: the Value of the Renaissance Past in Contemporary Culture - Dooley, Brendan (Peter Lang AG, Internationaler Verlag der Wissenschaften, 2014)
This volume directs a transdisciplinary gaze on the field of Renaissance Studies as currently practised in Europe, North America and beyond. The concept of the Renaissance as applied to a particular time and place is still regarded as being of central importance to the history of thought and culture. The essays collected here raise the question of the contemporary relevance of the Renaissance. What is the significance of doing Renaissance Studies now, not only in terms of the field per se, but in terms of what the field has to say to contemporary society? In the past, the field of Renaissance
Print version record
Keywords: Electronic books; Aufsatzsammlung; Geschichte; Rezeption; Renaissance; Geschichte 1420-1650; Kultur; Europa